Rotection of political rights of citizens Republik of Kazakhstan to hold meetings and rallies, demjnstratijns, marches and pikets (Journal of actual problems of jurisprudence, 2018)
Disadvantages and flows in the current legislation of the Republic of Kazakhstan is enough and these guickly and mildly lightly taken «by the order from the top», laws are often leading to interference between government and the people.The socio-political will of the citizens to the political system, it seems «a monstrous evil». The forms of political action of the citizens of the Republic of Kazakhstan are carried out by the same rules, that is governed by regulations of limited characters.Political rights Kazakhstan citizens for holding meeting, marches, demonstrations and peaceful assemblies can’t be limited and should be consistens with international law.Key words: political rights, peaceful citizen meeting, meeting, marches, pickets, demonstrations, international law, ratification.